Geguritan Nala Damayanti Analisis Pendekatan Feminisme dan Nilai-Nilai Yang Terkandung - Ary Anggreni, Ni Putu Vivi; Suteja, I Wayan; Suardiana, I Wayan (Stilistika : Journal of Indonesian Language and Literature, 2023)
This study examines Geguritan Nala Damayanti . The purpose of this study is to describe feminism and the values contained in the Geguritan Nala Damayanti text. This study uses the theory of feminism according to Sugihastuti and Suharto. The stage of providing data using the listening method is assisted by translation techniques and recording techniques. The data analysis phase used qualitative methods assisted by analytical descriptive techniques. The stage of providing the results of data analysis using informal methods supported by inductive and deductive techniques. Feminism obtained from the research is how a woman experiences gender oppression and injustice in the form of marginalization, subordination, stereotypes, and violence that she experiences. As well as female figures who are used as role models and the values contained in them can be taken.